(untitled) (Atlas Journal of Biology, 2022)
As many studies on other crops showed an acropetal decline of fruit-set and fruit size in the inflorescence, this paper investigates the effect of flower position in spikelets in the '˜Sukkary' variety of date palm on fruit-set and final fruit weight. Also studied was the best time to apply strand-cut (bunch cut) as an alternative to hand thinning, to increase final fruit weight. Hand thinning is a labor cost operation and worker productivity operation is one adult tree per day maximum. To study fruit-set in relation to fruit position, three types of pollen were used to pollinate female trees: new pollen harvested in March 2018, pollen stored for one year at room temperature (25-35° C), and pollen stored for two years at room temperature. Four weeks after pollination, fruits aborted and those non-aborted in every bunch were counted. Recording was done in every spikelet from proximal to distal. To study the effect of fruit position in spikelet on fruit weight, fresh pollen was used to pollinate 'Sukkary' females. Every two days, fruit weight was measured from pollination to harvest, and fruit growth pattern was drawn. An analysis of variance (ANOVA) was carried out for the final fruit weight in every spikelet part. This investigation showed no pattern in fruit-set or in final fruit weight when using new pollen. When pollinated with old pollen that was one and two years old, the proximal '˜Sukkary' flowers of the spikelets showed less fruit-set compared to those of the middle and distal part. This basipetal decline is explained by low viability of old pollen, combined with the basipetal opening of the spathes in date palm...